(PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN (Studi Kasus Pembangunan Gedung Serbaguna dan Sumur Bor Dalam Program Percepatan Pembangunan Infratsruktur Desa / Kelurahan Mandiri Di Kelurahan Sekijang Kecamatan Bandar Sei Kijang Kabupaten Pelalawan Tahun 2013) - Putri, Tri Ananda; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Background problems implementing the Infrastructure Development Acceleration Program / District Village Self In Sekijang Village District of Bandar Sei Kijang Pelalawan in 2013 was less than optimal implementation of the program in terms of public participation. With the approach of the implementation of the program of community empowerment means the entire process of implementation of activities (preparation, planning, implementation and post-implementation physical physically) active community participation listed on Pelalawan decree No. 63 of 2013.The research goal is to examine how community participation in every phase of activity in the Infrastructure Development Acceleration Program / District Village Self In Sekijang Village District of Bandar Sei Kijang Pelalawan in 2013.The study was conducted with a qualitative approach with descriptive type. Informants selected as samples, while the data collected by teknin interviews, observation and research documents as a source of research data.Based on the results of research through interviews, observation and document penulusuran. it can be seen that the lack of public participation in the implementation of the Program for the Acceleration of Infrastructure Development / District Village Self In Sekijang village district of Bandar Sei Kijang Pelalawan in 2013.Keywords: Community Participation, Rural Development / Village